Obesidad infantil y biodiversidad humana: El estado de la cuestión en México y Argentina - Marrodán Serrano, María Dolores; Moreno-romero, Susana; Nodarse Valdés, Nereyda; Rodríguez Ibañez, María Del Pilar; Aréchiga Viramontes, Julieta (Observatorio Medioambiental, 2007)
This paper reviews recent epidemiological studies of the prevalence of obesity in Latin American children. It shows results of the direct antropometric measurements of Susques and San Salvador de Jujuy populations, located at the northeast of Argentina, and Lomas de la Estancia, a popular ‘colonia’ located at the periphery of Mexico, City. Regardless of the international growth criteria used, the study found a great influence of the urbanization degree on the prevalence of childhood and adolescent obesity.